2018
DOI: 10.1016/j.actatropica.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A fine scale eco-epidemiological study on endemic visceral leishmaniasis in north ethiopian villages

Abstract: Graphical abstractHypothetical illustration of Anthroponotic Transmission Cycle of L. donovani in VL Endemic Villages in Northern Ethiopia. Transmission of L. donovani occurs anthroponotically in or close to households near to vertisols. Sand flies breeding in vertisols, are attracted into villages to feed blood on domestic animals, plant communities my serve as resting places for sand fly vectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The collective studies in Sudan and NW Ethiopia lead to the consensus that P . orientalis has a low propensity to enter household buildings [ 17 , 21 , 25 , 26 , 27 , 28 , 53 , 54 ], which is corroborated by the current data showing that comparatively few P . orientalis were captured inside sleeping huts as measured by chemical knockdown (KD) methods.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The collective studies in Sudan and NW Ethiopia lead to the consensus that P . orientalis has a low propensity to enter household buildings [ 17 , 21 , 25 , 26 , 27 , 28 , 53 , 54 ], which is corroborated by the current data showing that comparatively few P . orientalis were captured inside sleeping huts as measured by chemical knockdown (KD) methods.…”
Section: Discussionsupporting
confidence: 89%
“…In East Africa, the prominent VL vector is Phlebotomus orientalis , which thrives in remote woodlands, villages, and peridomestic habitats, characterized by the presence of black cotton soil and Acacia seyal and Balanites aegyptiaca trees [ 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The vector is highly exophilic and exophagic, rarely captured inside household buildings [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] with villagers being exposed outdoors in the household compound and in the peridomestic surroundings. Phlebotomus orientalis is a highly seasonal species.…”
Section: Introductionmentioning
confidence: 99%
“…In northern Ethiopia (Fig. 1), we used rbcL PCR to identify plants consumed by wild-caught Phlebotomus orientalis, the local vector of visceral leishmaniasis (VL) (20). We extracted DNA from 804 sand flies, achieved rbcL amplification in 65 of them, and sequenced the rbcL amplicons from 36 ( Table 1 and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In India, the probability or seroreversion has varied between 0 and 87% by 12 months [20, 27, 28]. In Ethiopia, a recent study amongst the general population in northern Ethiopia reported that 71% of DAT-positive individuals seroreverted by 12 months [29]. High rates of LST reversion have also been observed in the South of Ethiopia [11].…”
Section: Discussionmentioning
confidence: 99%